Mechanical and electrical properties of 3D-printed acrylonitrile butadiene styrene composites reinforced with carbon nanomaterials - Weaver, Abigail (Kansas State University, 2017)
3D-printing is a popular manufacturing technique for making complex parts or small quantity batches. Currently, the applications of 3D-printing are limited by the material properties of the printed material. The processing parameters of commonly available 3D printing processes constrain the materials used to a small set of primarily plastic materials, which have relatively low strength and electrical conductivity. Adding ﬁller materials has the potential to improve these properties and expand the applications of 3D printed material. Carbon nanomaterials show promise as ﬁller materials due to their extremely high conductivity, strength, and surface area. In this work, Graphite, Carbon Nanotubes, and Carbon Black (CB) were mixed with raw Acrylonitrile Butadiene Styrene (ABS) pellets. The resulting mixture was extruded to form a composite ﬁlament. Tensile test specimens and electrical conductivity specimens were manufactured by Fused Deposition Method (FDM) 3D-printing using this composite ﬁlament as the feedstock material. Weight percentages of ﬁller materials were varied from 0-20 wt% to see the eﬀect of increasing ﬁller loading on the composite materials. Additional tensile test specimens were fabricated and post-processed with heat and microwave irradiation in attempt to improve adhesion between layers of the 3D-printed materials. Electrical Impedance Spectroscopy tests on 15 wt% Multiwalled Carbon Nanotube (MWCNT) composite specimens showed an increase in DC electrical conductivity of over 6 orders of magnitude compared to neat ABS samples. This 15 wt% specimen had DC electrical conductivity of 8.74x10−6 S/cm, indicating semi-conducting behavior. MWCNT specimens with under 5 wt% ﬁller loading and Graphite specimens with under 1 wt% ﬁller loading showed strong insulating behavior similar to neat ABS. Tensile tests showed increases in tensile strength at 5 wt% CB and 0.5 wt% MWCNT. Placing the specimens in the oven at 135 °C for an hour caused increased the stiﬀness of the composite specimens.
Keywords: Fused Deposition Modeling; Carbon nanomaterials; Nanocomposites; Tensile properties; Acrylonitrile butadiene styrene composites; Additive manufacturing